APLIKASI KUESIONER ONLINE UNTUK EVALUASI PEMBELAJARAN DI MADRASAH TSANAWIYAH MAHDALIYAH JAMBI: OnlineQuestionnaire, Learning Evaluation, Madrasah Tsanawiyah, Educational Technology - Nurjani, Yeni; Mulyadi, Mulyadi; Satria, Eza Dwi (FORTECH (Journal of Information Technology), 2025)
This study aims to develop an online questionnaire application that can be used as a learning evaluation tool at Madrasah Tsanawiyah Mahdaliyah. The application is designed to replace manual methods, which are time-consuming and prone to errors. The development process utilizes technologies such as HTML, CSS, JavaScript, PHP, and MySQL to create an efficient and user-friendly system. Application testing was conducted among students and teachers to ensure ease of use and data accuracy. The development results indicate that the application facilitates the questionnaire data collection process, speeds up analysis, and produces more accurate learning evaluation reports. This application is expected to provide a practical solution for improving the quality of learning evaluations in educational institutions.